Implementasi Pengelolaan Tanah di Desa Adat Kerobokan untuk Kegiatan Industri Pariwisata - Julianti, Lis; Sudirga, I Made (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 12 No 2 (2023), 2023)
This study aims to find and examine the implementation of land management in the Kerobokan Traditional Village for tourism industry activities. The issues raised in this study are about mechanisms and procedures for land management and the implementation of land management in traditional villages for the tourism industry. This research is an empirical research with an emphasis on field data as primary data. This study found that the implementation of land management in the Kerobokan Traditional Village for tourism industry activities was carried out by leasing a contract based on an agreement through the relevant Paruman Desa Adat/Banjar Adat. The Kerobokan Traditional Village also has a Perarem Pangele which regulates administrative provisions that must be met by krama tamiu (in this case including investors). The authority to manage this land is strengthened by the Regional Regulation of the Province of Bali Number 4 of 2019 concerning Traditional Villages in Article 1 number 8 which provides autonomy for Traditional Villages to manage their own households. Penelitian ini bertujuan untuk menemukan dan mengkaji terkait implementasi pengelolaan tanah di Desa Adat Kerobokan untuk kegiatan industri pariwisata. Permasalahan yang diangkat dalam penelitian ini adalah tentang mekanisme dan prosedur pengelolaan tanah serta implementasi pengelolaan tanah di Desa Adat untuk industri pariwisata. Penelitian ini merupakan penelitian empirik dengan menekankan pada data lapangan sebagai data primer. Penelitian ini menemukan bahwa implementasi pengelolaan tanah di Desa Adat Kerobokan untuk kegiatan industri pariwisata dilakukan dengan sewa kontrak berdasarkan kesepakatan melalui Paruman Desa Adat/Banjar Adat yang bersangkutan. Desa Adat Kerobokan juga memiliki Perarem Pangele yang mengatur tentang ketentuan administrasi yang harus dipenuhi oleh para krama tamiu (dalam hal ini termasuk investor). Kewenangan pengelolaan tanah tersebut diperkuat dengan Peraturan Daerah Provinsi Bali Nomor 4 Tahun 2019 tentang Desa Adat pada Pasal 1 angka 8 yang memberikan otonomi bagi Desa Adat untuk mengurus rumah tangganya sendiri.